(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
This article presents the "Pedagogy for the Desiring Voice," a vocal approach stemming from doctoral research conducted at the Federal University of Bahia (UFBA). The practice enhances the individualities of practitioners by awakening the conscious body. Divided between the physical and extracorporeal realms, it aims to expand bodily awareness, fostering a personal and authorial experience. By intertwining these spheres, the goal is to understand and grasp the body individually. The pillars of the pedagogy — thematic visualization, corporeal-vocal sensitization, and voice-dance — organize the practice.